Biogenic Fraction Determination in Fuel Blends by Laser‐Based 14CO2 Detection. Issue 3 (18th January 2021) - Delli Santi, Maria Giulia; Bartalini, Saverio; Cancio, Pablo; Galli, Iacopo; Giusfredi, Giovanni; Haraldsson, Conny; Mazzotti, Davide; Pesonen, Antto; De Natale, Paolo
Abstract : A widespread use of biofuels is a key recommendation of the Paris Agreement and leading international organizations. It is an important step to mitigate the global warming effects due to greenhouse‐gas emissions from fossil oils. To this aim, an analytical technique sufficiently cheap and compact, to foster its widespread adoption, is necessary. Herein, it is shown that a compact, laser‐based spectrometer is suitable to replace the few established techniques, which have been used to quantify the biofraction in fuel blends, so far. Measurements of the biogenic fraction in different fuel samples are reported, with a precision of 1% in the whole range (0–100%) of possible blends, confirming a performance comparable to the best existing technique. An onsite‐deployable saturated‐absorption cavity ring‐down (SCAR) spectrometer is used. The results demonstrate the potential of laser‐based instrumentation to do the accurate and precise measurements required for the certification of biogenic content of any hydrocarbon‐based material. Worldwide adoption of such laser‐based technology for biofraction certification can significantly boost the market of biofuels and can prove to be a disruptive methodology for assessing the biogenic content in plastics and polymeric materials. Abstract : Laser‐based ultrasensitive detection of radiocarbon dioxide is demonstrated to be a revolutionary approach for the determination of biogenic fraction in biofuels and, more generally, bio‐based materials. Fossil versus biogenic fraction accurate determination plays a fundamental role for climate change assessment and mitigation. In this respect, this novel laser‐based approach can prove to be game‐changing.